Comparison of triglyceride-glucose index and HOMA-IR as indicators of insulin resistance in obese women with subclinical hypothyroidism - Kirac, Cem Onur; Sirikci, Vehbi; Findikli, Huseyin Avni (Publishing Office of the University of Rzeszow, 2022)
Introduction and aim. Thyroid hormones play an important role in glucose metabolism as in many metabolic events. The aim of our study is to evaluate the relationship between subclinical hypothyroidism (SCH) and insulin resistance, especially in obese women. Material and methods. Newly diagnosed SCH patients with body mass index (BMI) ≥30 who applied to our outpatient clinic between March 2021 and October 2021, and euthyroid obese women who applied for routine control were included in the study. In this study, we used homeostasis model assessment of insulin resistance (HOMA-IR) and triglyceride glucose (TyG) indexes, which are noninvasive, simple and useful methods for evaluating insulin sensitivity. Results. The study included 78 female patients between the ages of 19 and 64. A correlational analysis was performed between thyroid stimulating hormone (TSH) and HOMA-IR, TyG, and BMI. The results showed that TSH levels were positively correlated with HOMA-IR (R=0.297, p=0.008), TyG (R=0.316, p=0.005) and BMI (R=0.307, p=0.006). This relationship was stronger for TyG compared to the other variables. As another finding, BMI was positively correlated with HOMA-IR (R=0.359, p=0.001) and TyG (R=0.404, p<0.001). This relationship was stronger for TyG than HOMA-IR. Conclusion. These results show that patients with SCH are at risk of developing diseases that accompany insulin resistance, such as metabolic syndrome and cardiovascular disorders. The most important finding of our study is that the TyG index gives more significant results than HOMA-IR, especially in obese women.
Study was approved by the institutional review board, and a waiver of authorization was given (Ethics Committee decision no: 02, date: 26.08.2022).
Keywords: HOMA-IR; insulin resistance; subclinical hypothyroidism; triglyceride-glucose index